Comparison of thermal maturation indicators within hydrocarbon bearing sedimentary rock - Kowal, David Anazario (Kansas State University, 2016)
The thermal maturity of hydrocarbon-rich source rocks can be estimated by several different methods. These methods focus on a specific geochemical or mineralogical aspect contained within the rock. Because each method has limitations, it is advisable to use several methods to better determine thermal maturation. This report summarizes two common methods used to determine thermal maturity, vitrinite reflectance and illitization. Vitrinite reflectance and illitization have both been shown to be effected by similar temperatures that are within the hydrocarbon generation window. In some previous studies these two methods give different levels of maturation when looked at in tandem. Formations such as the Woodford Shale of Oklahoma are made up almost completely of illite in the clay fraction, even at low levels of vitrinite reflectance. These are also without a clear source of potassium, which is often the limiting factor in the process of illitization. Totten et al. (2013) suggest that in place of potassium feldspars, which are a common source of K⁺ for illite (but lacking in the Woodford) that the needed K⁺ was provided by the organic material that was being altered under the same temperatures of the clay minerals. The Woodford contains large amounts of organic matter, This would be consistent with promoting illitization at lower thermal maturities than organic-poor shales.
Keywords: Geology; Thermal maturity; Illitization; Vitrinite reflectance; Geology (0372)